2020
DOI: 10.1177/1457496920938605
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Appendectomy is Safe and has Similar Outcomes as Daytime Appendectomy: A Study of 1198 Appendectomies

Abstract: Introduction: Although it is controversial whether appendectomy can be safely delayed, it is often unnecessary to postpone operation as a shorter delay may increase patient comfort, enables quicker recovery, and decreases costs. In this study, we sought to study whether the time of day influences the outcomes among patients operated on for acute appendicitis. Materials and Methods: Consecutive patients undergoing appendectomy at Tampere University Hospital between 1 September 2014 and 30 April 2017 for acute a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
4
13
0
Order By: Relevance
“…In terms of complication rates, this study confirmed the safety of nighttime appendectomy, with no significant differences between study groups. Similar to previous publications, the most common complication in both study groups was abscess formation [ 3 , 24 , 35 ]. Other postoperative complications such as ileus, wound infections, and bleeding at the trocar insertion site were less common.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In terms of complication rates, this study confirmed the safety of nighttime appendectomy, with no significant differences between study groups. Similar to previous publications, the most common complication in both study groups was abscess formation [ 3 , 24 , 35 ]. Other postoperative complications such as ileus, wound infections, and bleeding at the trocar insertion site were less common.…”
Section: Discussionsupporting
confidence: 87%
“…A recent meta-analysis clearly demonstrated that delayed laparoscopic appendectomy (up to 24 h) does not increase the likelihood of developing complications in simple appendicitis [ 23 ]. In addition, previously published results suggest that surgeons may defer appendectomy in patients with suspected simple appendicitis occurring at night [ 23 , 24 ]. Another recent study has shown that short deferral of appendectomy does not increase the risk of appendiceal perforation, but may be associated with a slightly increased risk of surgical site infections [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Monttinen et al. [ 29 ] in another study found that out of 1,198 patients, there was a 4.8 percent complication rate and a 0.2 percent death rate. This study also had a relatively large sample size of 1001 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Monttinen et al. showed that operations performed at night had a lower length of hospital stay [ 29 ]. Despite the increase in workload and sleepiness during the night shifts, a study by Tomasko and co-workers found that clinicians were able to perform surgeries proficiently and the rest of the staff were getting their tasks done correctly, and it also believes that operating at nighttime and having sleep deprivation does not decrease cognitive function but instead increases it [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Usually in mild cases patients can safely wait until the next morning. However, earlier surgery and symptom relief reduces length of hospital stay, improves patient satisfaction and also achieves cost-savings [14,15]. We demonstrated that complicated procedures are associated with higher rate of postoperative infections.…”
Section: Discussionmentioning
confidence: 76%